The inherent review jurisdiction of the supreme court - Taitz, Jerold Leonard (Centre for Law and Society, 2026)
This thesis concerns the inherent review jurisdiction of the Supreme Court. The remedy is isolated from, examined and compared with the (general) inherent jurisdiction of the Court. The purpose of the remedy is: • i) to control, supervise, or otherwise confine administrative authorities, · tribunals and voluntary associations to their respective enabling Acts, terms of reference or constitutions and to certain judicially required norms of conduct; ii) . to do justice in regard to the proceedings of inferior courts where no other remedy is available. The inherent review jurisdiction is not an appellate remedy. In the exercise of such. jurisdiction the Court will not interfere with merits of the decision a quo - it is concerned only with the validity of such decision. The remedy is examined under the following headings: .il its principal features; ii) the ground for its grant; iii) the various methods by which it may be invoked. Thereafter the remedy is evaluated. Although its importance is acknowledged, certain defects in the remedy are indicated. The remedy was not conferred upon the Court by legislation, yet by 1890 its existence. was acknowledged. The question of the origin of the remedy is raised not only for its academic interest but also for the possible, practical advantage of improving the remedy. The origin of the remedy was sought first in the Roman-Dutch procedural law period at the Cape (1652 - 1834). This enquiry showed that the source of the remedy is not to be found in this period or in the Roman Dutch law. Thereafter the origin was sought during the English procedural law period (from 1834). The remedy was unknown at the Cape in 1834 yet by 1890 it was fully acknowledged by the Cape Supreme CourL Accordingly this· period may be regarded as the gestation stage of the remedy. It was necessary, too, to investigate the relevant law, in England and in • the former Dutch colonies of Ceylon and those in South America (which be- , . . came British_ Guian~), during this period. Although the research showed certain similarities between the remedy and the (then) English writ of certiorari, neither the latter nor any other English remedy was found to be the direct source of the remedy at the Cape. Apart from its academic interest. the examination of the relevant law and the administration of Justice in Ceylon and strictish Guiana was of little pertinent value to· the research. Through the decided cases of the Cape Supreme Court, during the period 1834 - 1890, the origin of the remedy was ascertained. The remedy is found to be the result of judicial creativity; in other words, it is judge made. Accordingly, it is suggested that the defects in. the remedy are capable of rectification by the Court itself. The thesis concludes with a number of suggestions for the improvement of the remedy. These relate to i) The furnishing of reasons for the decision, a quo; ii) . the 'delay rule'; iii) the right to be heard in administrative proceedings and the ‘functional approach'; iv) 'judicial intervention resulting from an unreasonable act and in respect of an error of law; v) the extension of the remedy to certain company law situations.